1981
DOI: 10.1083/jcb.88.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy-induced increase of intermediate filaments in vascular smooth muscle.

Abstract: The distribution of filaments was studied in hypertrophied rabbit vascular smooth muscle . Hypertrophy was induced by partial ligation of the portal-anterior mesenteric vein . 14 d after ligation, there was an approximately threefold increase in the number of intermediate filaments per cross-sectional area, as compared to control values . The actin :intermediate:myosin filament ratio was 15 :1 .1 :1 in control and 15 :3 .5 :0 .5 in hypertrophied portal-anterior mesentric vein vascular smooth muscle . Compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 53 publications
2
30
1
Order By: Relevance
“…These latter cells were irregular in outline with the nuclei often eccentrically located, as we found with vascular smooth muscle cells. The lengths of cells dissociated from the rabbit portal mesenteric vein, 258 ^im (Berner et al, 1981), were greater than we found in the rat. This tissue (Komuro et al, 1982).…”
Section: Discussioncontrasting
confidence: 37%
“…These latter cells were irregular in outline with the nuclei often eccentrically located, as we found with vascular smooth muscle cells. The lengths of cells dissociated from the rabbit portal mesenteric vein, 258 ^im (Berner et al, 1981), were greater than we found in the rat. This tissue (Komuro et al, 1982).…”
Section: Discussioncontrasting
confidence: 37%
“…In an ultrastructural study of hypertrophic vascular smooth muscle cells in a partially ligated rabbit portal-anterior mesenteric vein, Berner et al 34 found that there was no net change in the number of myosin filaments per cell profile and that the increased volume of the cell was occupied by actin and intermediate filaments. This finding was in agreement with similar findings in the hypertrophic cells of the stenotic guinea pig intestine.…”
Section: Discussionmentioning
confidence: 99%
“…A lesser force-generating ability of vascular smooth muscle from hypertensive animals has long been recognized"- 21 22 and may be due in part to a decreased smooth muscle cell volume 23 or a decreased smooth muscle cell myosin content. 24 Conversely, Mulvany et al 25 and Whall et al 26 have reported that small mesenteric arteries from SHR generate more force than these arteries from normotensive animals. However, recent preliminary findings show that cerebral but not the mesenteric vessels from SHR had significantly lower myosin levels compared to the corresponding vessels from WKY.…”
Section: Figure 2 Isometric Force Recordings Of Isolated Basilar Artmentioning
confidence: 99%